Biomedical applications of fluorinated ionic liquids as drug delivery systems - Oliveira, Ana Luísa Sabina de (2022)
Tese de mestrado, Ciências Biofarmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.